Fabrication and Characterization of a 2 × 2 Microfiber Knot Resonator Coupler - Jasim, Ali Abdulhadi (IOP Publishing, 2012)
A 2 × 2 microfiber knot resonator (MKR) coupler is demonstrated. The hybrid device is obtained by forming a knot within the coupling region of a microfiber coupler with a 50:50 splitting ratio. The microfiber coupler is successfully fabricated by laterally fusing and tapering two optical fibers using a flame-brushing technique. The coupler has an overlapping length of 40 mm with a uniform waist of around 5 μm. With an MKR structure, the coupler produces a resonant response at both output ports. The free spectral range of the output spectrum from both ports is obtained at 0.2 nm at a knot diameter of 260 μm. The resonance extinction ratio of the device varies from 2 to 6 dB while the calculated Q factor and finesse are ∼25646 and 3.3, respectively, at both output ports.